Crashworthiness optimization of automotive parts with tailor rolled blank. (15th August 2018) - Sun, Guangyong; Tian, Jun; Liu, Tangying; Yan, Xiaolei; Huang, Xiaodong
Highlights: A crashworthiness optimization algorithm for tailor rolled blank (TRB) structures is proposed. Crashworthiness designs for TRB top-hat column and bumper beam are fulfilled. The improvements of optimized TRB parts are presented. Abstract: Tailor rolled blank (TRB) as an advanced manufacturing process developed recently has broad application prospects in automotive and aerospace industries for its significant advantages in better load-carrying ability and lighter mass. TRB is a typical custom product, whose performance is closely related to its thickness variation, thus how to obtain the optimal thickness variation of a TRB part becomes a challenging task, especially for crashworthiness design. To address this issue, an optimization method based on the variation of wall thickness is presented to maximize the energy absorption capacity of TRB parts. Firstly, finite element (FE) models of two typical automotive parts, TRB top-hat column and TRB bumper beam, are established and validated through crushing experiments. Then a heuristic optimization method is proposed based on the general assumption that more mass enables to absorb more energy. The elemental energy density is used to optimize structural thickness distribution of geometrical and material nonlinear structures. Numerical results demonstrate the capability and effectiveness of the proposed optimization method for achieving the best thickness layout of automotive TRB parts for crashworthiness.